A systematic review and meta‐analysis of exercise interventions for colorectal cancer patients. (8th July 2013) - Cramer, H.; Lauche, R.; Klose, P.; Dobos, G.; Langhorst, J.
<x xml:space="preserve">Abstract</x> The aim of this systematic review and meta‐analysis was to investigate the effectiveness of exercise for colorectal cancer patients. Pubmed/Medline, Scopus and the Cochrane Library were searched through December 2012 without language restrictions. Randomised controlled trials (RCTs) comparing exercise interventions to control conditions were analysed when they assessed health‐related quality of life, fatigue, physical fitness, survival and/or tumour‐associated biomarkers in colorectal cancer patients. Risk of bias was assessed using the risk of bias tool recommended by the Cochrane Back Review Group. Literature search identified 342 non‐duplicate records of which five RCTs with a total of 238 patients were included; three RCTs had low risk of bias. No evidence was found for short‐term effects on quality of life [standardised mean difference (SMD) = 0.18; 95% confidence interval (CI) −0.39, 0.76; P = 0.53] or fatigue (SMD = 0.18; 95% CI −0.22, 0.59; P = 0.38). There was strong evidence for short‐term improvements of physical fitness after aerobic exercise compared with controls (SMD = 0.59; 95% CI 0.25, 0.93; P < 0.01). One RCT each assessed immune parameters and oxidative DNA damage. No study reported survival rates or safety data. Given this insufficient evidence and the lack of safety data, no recommendation can be made regarding exercise interventions as a routine intervention for colorectal cancer patients.